O direito adentra a cozinha: estudo sobre a proteção autoral de criações culinárias - Medrado, André Rivail (2016)
In this study, starting from the question about the possibility to qualify cooking as art, we analyze to what extent the Copyright Law would apply to the protection of culinary creations. The chefs are often referred to as artists, but little attention has been given to the aesthetic-philosophical foundation of this assignment, i.e., if effectively makes sense to qualify a culinary creation as art. The initial hypothesis of this paper is that, justified the art nickname to culinary activity, its product should therefore deserve the same protection as to the intangible property subjected to Copyright. However, in order to grant a more complete treatment of the topic discussed, we extended the initial scope, so as to evaluate also other institutes of intellectual property – namely, the trademarks, the trade dress, the industrial design, the patent and the trade secret – as potentially useful legal tools to protect different aspects or elements of the culinary creations. The study included two field research tools: one qualitative, which consisted of twenty interviews with qualified and renowned chefs in the gastronomic segment, based on a eleven semi-structured questions; and other quantitative, which consisted in the application of questionnaires to 86 chefs.